Surgical treatment for tibialis posterior dysfunction. (April 2009) - Edwards, Max R; Southgate, Crispin RW; Jack, Christopher; Singh, Samrendu K
Dysfunction of the tibialis posterior tendon is the most common cause of acquired flatfoot deformity in adults. Early treatment with orthotics may often prevent progression of the dysfunction into a fixed deformity. Late presentation or failure of conservative measures may need to be corrected by surgical means. In this review we will discuss the anatomy, etiology, diagnosis and treatment of tibialis posterior dysfunction. Surgical options for dealing with patients who have failed nonoperative measures will be covered, outlining outcomes, recent advances and future directions in the treatment of this complex disorder.